Emergence and divergence of major lineages of Shiga-toxin-producing Escherichia coli in Australia. Issue 5 (20th May 2019) - Ingle, Danielle J.; Gonçalves da Silva, Anders; Valcanis, Mary; Ballard, Susan A.; Seemann, Torsten; Jennison, Amy V.; Bastian, Ivan; Wise, Rolf; Kirk, Martyn D.; Howden, Benjamin P.; Williamson, Deborah A.
Abstract : Shiga-toxin-producing Escherichia coli (STEC) infection is an important global cause of foodborne disease. To date however, genomics-based studies of STEC have been predominately focused upon STEC collected in the Northern Hemisphere. Here, we demonstrate the population structure of 485 STEC isolates in Australia, and show that several clonal groups (CGs) common to Australia were infrequently detected in a representative selection of contemporary STEC genomes from around the globe. Further, phylogenetic analysis demonstrated that lineage II of the global O157:H7 STEC was most prevalent in Australia, and was characterized by a frameshift mutation in flgF, resulting in the H-non-motile phenotype. Strong concordance between in silico and phenotypic serotyping was observed, along with concordance between in silico and conventional detection of stx genes. These data represent the most comprehensive STEC analysis from the Southern Hemisphere, and provide a framework for future national genomics-based surveillance of STEC in Australia.